Keputusan Melakukan Mobilitas Penduduk dan Dampaknya Terhadap Pendapatan Migran di Kota Denpasar - Martini, Ni Putu Rahayu; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 2, Februari 2013 (pp. 63-118), 2013)
Population mobility from rural to urban areas is basically an economic phenomena that hit developing countries. A wide range of factors behind a decision making process by migrant population mobility to urban areas. This study covered 82 migrants residing in the Pdangsambian Village, West Denpasar District. The techniques of data analyze used logistic regression analysis showed that the independent variables used overall significant effect on decision to perform nonpermanent mobility. Impact of population mobility tested with “different test” showed a significant positive impact on migrant income. Some of efforts needed to reduce the rate of mobility of the population to urban areas by improving rural infrastructure until development gap between in rural and urban area can be overcome. Keywords : decision making, population mobility, income
Keywords: decision making, population mobility, income